Recharge to contribute: Psychological Detachment as a Pathway from Perceived Organizational Support to Citizenship Behaviour and Subjective Well-being - Putri Ramadhani Salim; Alice Selendu (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2026)
Healthcare workers face high job demands, limited medical resources, the need to provide high-quality care, and complex emotional pressures, all of which have the potential to undermine their well-being and work behavior. This study aims to examine the role of psychological detachment as a mediator in the relationship between perceived organizational support and subjective well-being and organizational citizenship behavior among healthcare workers. This study employs a quantitative approach using a cross-sectional survey design. The study sample consisted of 432 healthcare workers employed at various healthcare facilities. Data were collected using a questionnaire that measured perceived organizational support, psychological detachment, subjective well-being, and organizational citizenship behavior. Data analysis was conducted using Partial Least Squares-based Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS 4 software. The results indicate that perceived organizational support has a positive and significant effect on psychological detachment. Psychological detachment also has a positive effect on subjective well-being and organizational citizenship behavior. Furthermore, psychological detachment was found to act as a mediator in the relationship between perceived organizational support and these two variables. These findings suggest that the organizational support perceived by healthcare workers can enhance psychological well-being and prosocial behavior in the workplace through individuals’ ability to detach from work demands. The implications of this study underscore the importance of healthcare organizations in creating a work environment that supports the psychological recovery of healthcare workers in order to improve their well-being and performance.Tenaga kesehatan menghadapi tuntutan kerja yang tinggi, keterbatasan sumber daya tenaga medis, intensitas pelayanan yang berkualitas, serta tekanan emosional yang kompleks sehingga berpotensi menurunkan kesejahteraan dan perilaku kerja. Penelitian ini bertujuan untuk menguji peran psychological detachment sebagai mediator dalam hubungan antara perceived organizational support dengan subjective well-being dan organizational citizenship behavior pada tenaga kesehatan. Penelitian ini menggunakan pendekatan kuantitatif dengan desain survei cross-sectional. Partisipan penelitian berjumlah 432 tenaga kesehatan yang bekerja di berbagai fasilitas pelayanan kesehatan. Data dikumpulkan menggunakan kuesioner yang mengukur perceived organizational support, psychological detachment, subjective well-being, dan organizational citizenship behavior. Analisis data dilakukan menggunakan Structural Equation Modeling berbasis Partial Least Squares (PLS-SEM) dengan bantuan perangkat lunak SmartPLS 4. Hasil penelitian menunjukkan bahwa perceived organizational support berpengaruh positif dan signifikan terhadap psychological detachment. Psychological detachment juga berpengaruh positif terhadap subjective well-being dan organizational citizenship behavior. Selain itu, psychological detachment terbukti memediasi hubungan antara perceived organizational support dan kedua variabel tersebut. Temuan ini menunjukkan bahwa dukungan organisasi yang dirasakan tenaga kesehatan dapat meningkatkan kesejahteraan psikologis dan perilaku prososial di tempat kerja melalui kemampuan individu untuk melepaskan diri dari tuntutan pekerjaan. Implikasi penelitian ini menekankan pentingnya organisasi kesehatan dalam menciptakan lingkungan kerja yang mendukung pemulihan psikologis tenaga kesehatan guna meningkatkan kesejahteraan dan kualitas kinerja mereka.